Cat-D: a targeted sequencing method for the simultaneous detection of small DNA mutations and large DNA deletions with flexible boundaries. Issue 1 (December 2017) - Hong, Ru; Chandola, Udita; Zhang, Li-Feng
Abstract We developed a targeted DNA sequencing method that is capable of detecting a comprehensive panel of DNA mutations including small DNA mutations and large DNA deletions with unknown/flexible boundaries. The method directly identifies the large DNA deletions (Cat-D) without relying on sequencing coverage to make the genotype calls. We performed the method to simultaneously detect 10 small DNA mutations in β-thalassemia and 2 large genomic deletions in α-thalassemia from 10 genomic DNA samples. Cat-D was performed on 8 genomic DNA samples in duplicate. The 18 Cat-D samples were combined in one sequencing run. In total, 216 genotype calls were made, and 215 of the genotype calls were accurate. No false negative genotype calls were made. One false positive genotype call was made on one target mutation in one experimental duplicate from a genomic DNA sample. In summary, Cat-D can be developed into a robust, high-throughput and cost-effective method suitable for population-based carrier screens.